Boiling pressure drop, local heat transfer distribution and critical heat flux in horizontal straight tubes. (October 2017) - Hardik, B.K.; Kumar, Gajendra; Prabhu, S.V.
Highlights: Experimental data is reported for CHF in horizontal straight tubes. Local heat transfer coefficient is analysed along the axial length of tube. Wall and bulk fluid temperature distribution is analysed in the flow boiling system. Correlations are suggested for boiling pressure drop and CHF. Correlation is suggested for local heat transfer coefficient. Abstract: The objective of the present work is to measure the heat transfer and pressure drop in flow boiling with refrigerant R123 as the working medium. Local heat transfer coefficient along the axial length of tube and overall averaged heat transfer coefficient are compared with available correlations. In the present study, spatial variation in heat transfer coefficient along the axial length of tube is analysed with the increase of quality. Variation in heat transfer coefficient in different flow boiling region i.e. subcooled, nucleate and convective is studied. The experiments are conducted with seven test sections made of SS304 having four different tube diameters 5.5 mm, 7.5 mm, 9.5 mm and 12.0 mm with two different heated lengths 500 mm and 1000 mm. The system pressure is varying from 1.3 bar to 3.2 bar. The experimental data of two-phase pressure drop and critical heat flux are compared with available correlations. Correlations are suggested to measure the local heat transfer coefficient during boiling process, two-phase pressure drop and critical heat flux. Data of critical heat flux are published to contribute in the data bank for horizontal straight tubes.